Comovements and Structural Factors of Macroeconomic Volatility in Developing and Transition Economies: A Dynamic Panel Data Approach - OUECHTATI, Ichraf; ZAOUALI, Amira (Asian Economic and Financial Review, 2013)
This study examines the comovements of some economic variables and explores the structural factors of macroeconomic volatility in developing and transition economies, using dynamic panel technique. According to an analysis of variance and covariance, we conclude that macroeconomic volatilities are higher in these countries compared to developed economies and consumption volatilities exceed those of production in developing and transition economies. This finding shows that these countries don’t maintain their behaviour of consumption smoothing. This, consequently, implies a proof of failure of their financial markets. Using data for 44 countries during 1960- 2010, our GMM estimation results indicate that government expenditures, consumption and GDP volatilities are the major determinants of macroeconomic volatility. The most influential external factors on macroeconomic fluctuations are terms of trade and commercial opening volatilities.